KAJIAN OPERASIONAL PENGANGKUTAN SAMPAH DI KECAMATAN DENPASAR TIMUR - WIRAATMAJA, I PUTU PRANA; Suarna, I Wayan; Sudana, Ida Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 1 (2012), 2012)
Collection and transportation of waste in the Distiict of East Denpasar have not run optimally due to lack of garbage collection and waste transport processes which are 1101 adequate. The research was conducted with a S\1tvey to determine the condition of existing operational waste transportation route followed by following the waste transport vehicles and calculate the time it takes to make one trip transportation and the number of trips in one day. The number of vehicles Uiat will be surveyed in the field is the number of vehicles that serve the Sef'\ ???? ce area of East Dcnpasar DistJ·ict, which consists of dump trucks and arm roll truck. The results showed that the waste transportation operations in the District of East Denpasar have not nm optimally due to lack of bins for the community and a fleet of garbage that is not proportional to the volume of waste generated, the number of transport trip has not been able to reduce the waste. Transport route selection is currently not effective because it ha ???? not minimized the di ???? -tance and travel time. The condition of access to TPA Sarbagita is unfit to be passed by a garbage truck, where the bumpy road conditions can cause damage and inhibit the rate of truck components.
Keywords: transport of waste, landfill Sarbagita access point